1991
DOI: 10.1136/jnnp.54.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Excessive sweating: an uncommon sign of basilar artery occlusion.

Abstract: Excessive sweating of the face and, to a lesser degree, of the thorax and limbs, occurred after basilar artery occlusion in a 15 year old Saudi boy. Magnetic resonance imaging (MRI) showed a limited bilateral paramedian infarction of the rostral ventral pons. Basilar artery occlusion in children and adolescents is a rarity. Excessive sweating following such a stroke is rare in any age group. Clinico-anatomical correlations are discussed.Signs and symptoms of basilar artery occlusion are described in many artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Contralateral hyperhidrosis has been described both in patients with medullary and pontine brain stem infarction [56][57][58], as well as in a patient with a large infarction located in the territory of the posterior cerebral artery [59]. There is also one case report describing a patient with bilateral excessive sweating after basilar artery occlusion [60].…”
Section: Sweating Disordersmentioning
confidence: 97%
“…Contralateral hyperhidrosis has been described both in patients with medullary and pontine brain stem infarction [56][57][58], as well as in a patient with a large infarction located in the territory of the posterior cerebral artery [59]. There is also one case report describing a patient with bilateral excessive sweating after basilar artery occlusion [60].…”
Section: Sweating Disordersmentioning
confidence: 97%
“…It has been suggested that the pathway follows the pyramidal tract, 16 a hypothesis that is supported by the present study in that a clear-cut association was established between hyperhidrosis and various signs of pyramidal tract lesion (extensor plantar response, abnormal muscle tone, and degree of motor deficit). Further evidence for an association of the pathway with the pyramidal tract is derived from the report of Awada et al, 17 who described a patient with excessive bilateral sweating after basilar artery occlusion. Magnetic resonance imaging showed a paramedian infarct at the upper pontine level damaging the corticospinal tracts.…”
Section: Forehead Chest Forearm Hand Footmentioning
confidence: 99%
“…Contralateral hyperhidrosis may be observed in late phase of Lateral Medullary Infarct and is likely due to lesions of sympathetic pathway passing through lateral medulla [3] . Excessive sweating from cerebral infarct [2,4] , hypothalamus [5] , Pons [6,7] , and spinal cord [8] is also reported in the literature. Excessive sweating as an uncommon sign of basilar artery occlusion is described by Awada et al [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Excessive sweating from cerebral infarct [2,4] , hypothalamus [5] , Pons [6,7] , and spinal cord [8] is also reported in the literature. Excessive sweating as an uncommon sign of basilar artery occlusion is described by Awada et al [7] . Contralateral hyperhidrosis after cerebellar infarct and bilateral pontine infarct is described by Kim BS and associates [9] .…”
Section: Discussionmentioning
confidence: 99%